Tito and His Courtiers. Jože Pirjevec, Tito, ze słoweńskiego przełożyły J. Pomorska, J. Sławińska, Wydawnictwo Akademickie SEDNO, Warszawa 2018, 847 s. - Darasz, Zdzisław (Poznańskie Studia Slawistyczne, 2018)
This paper discusses Jože Pirjevec’s biography of Josip Broz, nicknamed Tito, Yugoslav leader from 1943 (when a Democratic Federal Yugoslavia was proclamed) until his death in 1980. The author focusses on several key aspects of his life and political activity in Yugoslav and international communist structures, in World War II, when he was the commander of the partisants, in the Non-Aligned Movement which was established in Belgrade (1961), and on the others fields. Through the personality of the great dictator and statesman Pirjevec’s work brings a valuable contribution to the discourse about anatomy of power.